EDUKASI PENDIDIKAN KESETARAAN GENDER UNTUK MENCIPTAKAN RELASI SEHAT DAN HARMONIS - Setiawan, Antonius Ian Bayu; Setyandari, Setyandari; Tyas, Prias Hayu Purbaning (Universitas katolik Musi Charitas, 2025)
Purpose: Cases of violence against women continue to require serious attention from multiple stakeholders, particularly in relation to limited understanding of gender equality within families and intimate relationships. Unequal power relations between men and women often position women in subordinate roles within households, increasing vulnerability to gender-based violence. This community service activity aims to strengthen understanding of gender equality as a foundation for fostering healthy, equitable, and harmonious relationships. Design/Methodology/Approach: The activity was implemented using a Participatory Action Research (PAR) approach, which emphasizes active community involvement throughout the intervention process. The program was structured into four main stages: exploration, planning, implementation, and reflection and evaluation. This approach enabled participants to engage critically with gender-related issues while actively contributing to problem identification and solution development. Findings: A total of 28 participants, consisting of mothers and adolescents, were involved in the activity. Participants were divided into three groups and received differentiated interventions tailored to their characteristics and needs. The results indicate an improvement in participants’ understanding of gender equality following the intervention, as reflected through group discussions, reflective activities, and evaluation outcomes. Practical Implications: The intervention applied a group guidance model that emphasizes group dynamics, shared reflection, and collective learning. This model proved effective in enhancing participants’ awareness of gender-equitable relationships and promoting attitudes that support mutual respect and non-violent interactions within families and communities. Originality/Value: This community service program offers a participatory and context-sensitive model for gender equality education that integrates group guidance with PAR principles. The intervention contributes to promoting gender-just behavior at the community level and supports broader efforts to prevent and reduce cases of violence against women.